(untitled) (Research, Society and Development, 2025)
The development of equipment that simulates functional movement patterns has expanded training options, with stair simulators standing out as tools that demand high metabolic effort while providing low joint impact. However, studies on the acute effects of this modality are still lacking, especially regarding differences between men and women. The aim of this study was to analyze the energy expenditure of a 20-minute session on the Lion Fitness Stair Simulator in physically active young adults. Thirty participants (15 men and 15 women) took part in a protocol consisting of warm-up, a main phase with progressive intensity up to 5 floors/minute, and cooldown. Energy expenditure was measured by direct ergospirometry, and heart rate was continuously monitored. The results showed significantly higher energy expenditure in men (378 ± 20 kcal) compared to women (323 ± 18 kcal; p = 0.003). No relevant differences were found in mean heart rate or perceived exertion, suggesting similar relative intensity between sexes. In conclusion, a single session on the stair simulator is effective and safe to induce high caloric expenditure in a short period, approaching daily physical activity recommendations for weight control and cardiovascular health. The equipment shows applicability in conditioning, rehabilitation, and health promotion programs.